PENGARUH MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN PERUMDA AIR MINUM KOTA MAKASSAR - Putri, Andi Nurmaulidya; Anwar; Natsir, Uhud Darmawan; Hasbiah, Siti; Hamka, Rezky Amalia (Universitas Putera Batam, 2024)
The purpose of this study was to determine the effect between motivation on job satisfaction of employees of Perumda Air Minum Makassar City and analyze the role of motivation in job satisfaction of employees of Perumda Air Minum Makassar City. This research is a quantitative descriptive research. The independent variable in this study is the motivation variable, while the dependent variable is employee satisfaction. The population in this study were 258 employees of Perumda Air Minum Makassar city. while the sample amounted to 80 people. The research data was obtained by giving a questionnaire. The data analysis technique is the simple linear regression test. Based on the results of data analysis, it is concluded that there is a positive and significant effect of motivation on job satisfaction of employees of Perumda Air Minum Makassar City. Motivation and job satisfaction are interrelated and influence each other. Employees who feel motivated tend to be more satisfied with their jobs because they feel that the efforts they make are recognized and appreciated. So that a company must be able to increase employee motivation so that employee satisfaction can increase and company goals can be achieved easily.